When Gambling for Resurrection is Too Risky - Kirti, Divya (IMF Working Papers; Working Paper ;, 2017)
Rather than taking on more risk, US insurers hit hard by the crisis pulled back from risk taking, relative to insurers not hit as hard by the crisis. Capital requirements alone do not explain this risk reduction: insurers hit hard reduced risk within assets with identical regulatory treatment. State level US insurance regulation makes it unlikely this risk reduction was driven by moral suasion. Other financial institutions also reduce risk after large shocks: the same approach applied to banks yields similar results. My results suggest that, at least in some circumstances, franchise value can dominate, making gambling for resurrection too risky.